2004
DOI: 10.1603/0022-2585-41.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Ixodes ricinusDensity, and Distribution and Prevalence ofBorrelia burgdorferiSensu Lato Infection Along an Altitudinal Gradient

Abstract: In this study, we measured the phenology of Ixodes ricinus ticks and their infection with Borrelia burgdorferi sensu lato (sl) simultaneously along an altitudinal gradient to assess the impact of climate on the phenology of ticks and on their infection with B. burgdorferi sl. From 1999 to 2001, free-living I. ricinus ticks were collected monthly by flagging vegetation at three different altitudes (620, 740, and 900 m above sea level) on the slope of a mountain in Chaumont (Neuchâtel, Switzerland). I. ricinus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
119
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 44 publications
27
119
1
Order By: Relevance
“…Overall prevalence of infection by Borrelia (34.8%) was similar to that of another study conducted in the same area (32.7%) (Casati et al 2004). Infection prevalence in adults was higher (39.6%) than in nymphs (25.5%), as often described in Europe (Rauter and Hartung 2005) and Switzerland (Casati et al 2004, Jouda et al 2004. Similarly, adult infections consisted more frequently of Ͼ160,000 spirochetes than those of nymphs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall prevalence of infection by Borrelia (34.8%) was similar to that of another study conducted in the same area (32.7%) (Casati et al 2004). Infection prevalence in adults was higher (39.6%) than in nymphs (25.5%), as often described in Europe (Rauter and Hartung 2005) and Switzerland (Casati et al 2004, Jouda et al 2004. Similarly, adult infections consisted more frequently of Ͼ160,000 spirochetes than those of nymphs.…”
Section: Discussionsupporting
confidence: 83%
“…Genospecies prevalence was in line with what had been observed in the same area: B. afzelii (33.8%), B. burgdorferi s.s. (10.3%), B. garinii (32.1%), B. myamotoi (3.1%), and B. valaisiana (20.2%) (Casati et al 2004, Jouda et al 2004, Morán Cadenas et al 2007b, Gern et al 2010. The Borrelia genospecies were similarly distributed among males and females.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, in the Czech Republic during the early 1980s, I. ricinus was not found at elevations >700 m asl, while more recent surveys have found population at elevations up to 1100 m asl (Daniel et al, 2003). Similarly, in Switzerland, tick densities were found to decrease with elevation, suggesting an altitudinal limit to tick survival corresponding with decreasing temperatures (Jouda et al, 2004). Similarly, in Sweden, the distribution of ticks has moved northward (Lindgren et al, 2000).…”
Section: Ixodes Ricinus and Tick-borne Diseases In Europementioning
confidence: 95%
“…3. The percentage of high-fat fully hydrated (H&F), low-fat fully hydrated (L&F), and low-fat moderately hydrated (L&M) Ixodes ricinus ticks that walked towards the wet (light grey bars) or the dry end (white bars) of the arena after 2 h. common one (Casati et al 2004;Jouda et al 2004;Morán Cadenas et al 2007;Gern et al 2010;Herrmann and Gern, 2010). B. bavariensis (6·8%), formerly B. garinii OspA serotype 4, a newly described genospecies (Margos et al 2009), is reported for the first time in the area, although it was already described in Switzerland (Staatswald) (Hu et al 2001;Huegli et al 2002;Pérez et al manuscript submitted ).…”
Section: Borrelia Infection In Ticksmentioning
confidence: 99%